2005
DOI: 10.1111/j.1365-2117.2005.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Palaeogene igneous rocks reveal new insights into the geodynamic evolution and petroleum potential of the Rockall Trough, NE Atlantic Margin

Abstract: Data acquired from petroleum exploration well 164/7‐1 drilled in the UK sector of the Rockall Trough have yielded fresh insights into the igneous and thermal history of this frontier region. The well targeted a large four‐way dip closed structure of presumed Mesozoic age named ‘The Dome Prospect’. The structure is now known to have a magmatic, rather than a purely structural origin, which was the preferred pre‐well interpretation. The well encountered 1.2 km of Palaeocene age basaltic lavas, overlying Late Cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
107
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 96 publications
2
107
0
Order By: Relevance
“…The BVC is situated along one of the NW-SE 180 trending lineaments, the Brendan's Lineament, which likely controls the site of the igneous 181 centre (Fig. 1A) (Archer et al 2005). 182…”
Section: Brendan's Volcanic Centre (Bvc) and Regional Stratigraphy 174mentioning
confidence: 99%
“…The BVC is situated along one of the NW-SE 180 trending lineaments, the Brendan's Lineament, which likely controls the site of the igneous 181 centre (Fig. 1A) (Archer et al 2005). 182…”
Section: Brendan's Volcanic Centre (Bvc) and Regional Stratigraphy 174mentioning
confidence: 99%
“…The Early Palaeogene transient regional uplifts are from references in Table 2. The central igneous complexes and/or seamounts are modified from Bull & Masson (1996); Ritchie, Hitchen & Edwards (1997); Naylor et al (1999); Edwards (2002);Hitchen (2004); Archer et al (2005). Abbreviations: BJ -Bjørnøya; BJH -Bjørnøya High; CGFZCharlie Gibbs Fracture Zone; EEC -East Erlend Complex; FTF -Faroe Transform Fault; GFZ -Greenland Fracture Zone; JM -Jan Mayen; JMFZ -Jan Mayen Fracture Zone; JMR -Jan Mayen Ridge; MTFC -Møre-Trøndelag Fault Complex; RBRosemary Bank; SFZ -Senja Fracture Zone; UFZ -Ungava Fracture Zone; VV -Vestbrona Volcanic rocks; VVP -Vestbakken Volcanic Province; WEC -West Erlend Complex.…”
Section: A Tectonic Settingsmentioning
confidence: 99%
“…The Alpin Dome is an eastwards-trending anticline up to 150 km in length; onlap and thinning suggest growth during the Late Eocene and Oligocene (Tuitt et al 2010), with middle Miocene compression also suggested by Stoker et al (2005a) and Ritchie et al (2008). A domal structure drilled by well 164/7-1 is inferred to have an igneous origin (Archer et al 2005).…”
Section: Southern Faroe-shetland Basin To the Northern Rockall Basinmentioning
confidence: 99%